OS CENTROS LOGÍSTICOS E INDUSTRIAIS ADUANEIROS E A INTEGRAÇÃO TERRITORIAL NO ESTADO DE SÃO PAULO - Penha, Lucas Ferreira Rosa (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2009)
From August to December 2006, a provisional executive order has changed the procedures for setting up customs stations in the secondary zones (dry-ports) and created thereby a new category of customs enclosure: Custom Logistics and Industrial Centers (CLIA). They are bonded warehouses (located out of the primary zones, wich are airports and ports areas) where import and export procedures are performed. The provisional executive order established a “liberalization” of the sector by transferring the initiative of establishing such grounds to the private sphere. Before that, it was a government responsability, through bidding process. They are geographical objects with technical and normative “densities” chosen as an alternative way to the procedures of customs clearance. This paper aims to understand the territorial implications of these new structures in the State of São Paulo, in a period characterized by the dispersion and dissolution of the production process and the increasing importance of its circulation.